ANALISIS NILAI TAMBAH AGROINDUSTRI TAHU DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR (STUDI KASUS PADA USAHA TAHU LUTFI) - Nikmatul Aula; Ilma Satriana Dewi (UIR Press, 2023)
Tofu agro-industry is a business that has very good and profitable prospects. It is because tofu is the important food source that contains protein for the human body and has a great demand from many people. The study aimed to analyze the procurement of raw materials and supporting materials, production processes, production costs, production, prices, income, and efficiency of the tofu business and to analyze the added value of Lutfi's tofu business in Siak Hulu District, Kampar Regency. The research method used is the case study method on Lutfi's tofu agro-industry in Siak Hulu District, Kampar Regency. Data analysis used was analyzed using descriptive quantitative and qualitative analysis, business analysis, and added value analysis by the Hayami method. The results showed that the usage of soybean raw material was 200 kg/production process. The use of supporting materials was 1 bunch of wood, 0.5 liters of vinegar, and 10 liters of diesel fuel. Meanwhile, production technology still used simple tools. The total production cost was Rp. 4,013,096/production process with a total production of 68 buckets and a selling price per bucket of IDR 65,000. The net income received by owners per production process was IDR 11,856,904. The RCR value was 2.89, which means that Lutfi's tofu business is feasible to be developed. The added value of Lutfi's tofu business was IDR 10.810 with an output price of IDR 2.708/kg, the value-added ratio was 46% and the labor income was 235/kg.